Analisis Kualitas Air Irigasi Persawahan Kampung Pasang Surut Kampung Sungai Tengah Kecamatan Sabak Auh Kabupaten Siak - Sudirman, Sudirman; Siswanto, Siswanto; Handayani, Yohanna Lilis (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Kampung Sungai Tengah rice fields have a functional land area of ± 450 ha of a total land area of ± 800 ha. To meet the needs of irrigation water, the government makes long storage and the people of Kampung Sungai Tengah use water from the Siak River flow. Making long storage serves to collect water at high tide and then at low tide the floodgates are closed so that water in long storage does not flow back into the river. This study aims to analyze the effect of salinity levels in long storage and to analyze whether the distance from the point of collection has an effect on water quality. The parameters of the water quality test are salinity, pH, and water temperature. Field testing was carried out for 3 days with test points at the Siak River, sluice gates, and long storage. The results of field testing showed that water from the Siak River that entered the long storage at high tide experienced an increase in salinity levels with the highest value of 0.03 ppt. This shows that there is an increase in salinity at high tide but the increase is not large and the water is still included in the fresh water category, so that water entering long storage at high tide can be directly used for irrigation purposes without first settling for 24 hours. The pH value obtained during the test was consistent at 6.8, which means the water is still suitable for use for irrigation of rice fields. The water temperature during the test has a value that varies during the test with the highest temperature of 330 degrees which is because the test was carried out during the day with hot sun conditions.Keywords: Water quality, irrigation, salinity, long storage, Anova method